Deciphering the Genes for Taste Receptors for Fructose in Drosophila. - Uchizono, S.; Itoh, T.Q.; Kim, H.; Hamada, N.; Kwon, J.Y.; Tanimura, T. (Molecules and Cells, 2017)
Taste sensitivity to sugars plays an essential role in the initiation of feeding behavior. In Drosophila melanogaster, recent studies have identified several gustatory receptor (Gr) genes required for sensing sweet compounds. However, it is as yet undetermined how these GRs function as taste receptors tuned to a wide range of sugars. Among sugars, fructose has been suggested to be detected by a distinct receptor from other sugars. While GR43A has been reported to sense fructose in the brain, it is not expressed in labellar gustatory receptor neurons that show taste response to fructose. In contrast, the Gr64a-Gr64f gene cluster was recently shown to be associated with fructose sensitivity. Here we sought to decipher the genes required for fructose response among Gr64a-Gr64f genes. Unexpectedly, the qPCR analyses for these genes show that labellar expression levels of Gr64d and Gr64e are higher in fructose low-sensitivity flies than in high-sensitivity flies. Moreover, gustatory nerve responses to fructose in labellar sensilla are higher in Gr64d and Gr64f mutant lines than in mutant flies of the other Gr64a-Gr64f genes. These data suggest the possibility that deletion of GR64D or GR64F may indirectly induce enhanced fructose sensitivity in the labellum. Finally, we conclude that response to fructose cannot be explained by a single one of the Gr64a-Gr64f genes.